ANALISIS KARAKTER TANGGUNG JAWAB PADA SISWA KELAS IV - Meita Wida Ayu Prihastuti; Santa . (Universitas Pakuan, 2020)
ANALYSIS OF THE CHARACTER OF RESPONSIBILITY IN GRADE IV STUDENTSThis research is a qualitative research through a descriptive approach. The purpose of this study was to determine the character of responsibility in grade IV students. The subjects of this study were students in grades IV A and IV B at SDN Lawanggintung 2, even semester, 2019/2020 academic year. Based on the results of the analysis, it shows that the character of responsibility possessed by grade IV students at SDN Lawanggintung 2 includes carrying out tasks that are well received and full of readiness, completing things responsibly, doing tasks according to their abilities, thinking before acting and considering the consequences. exists, is responsible for attitudes, words and actions and is responsible for attitudes, words and actions. This happens because of habituation to be able to shape the character of student responsibility which is carried out in school.